Risk management at universities: illegal residents in hostels & fire cases - Barzak, Omar Mokhles; Bawazir, Mohammed A.; Salah, Mohammed A. F.; Ibrahim, Jamaludin (IJCTT Journal, 2014)

(untitled)
Every organization/institution is exposed to some kinds of risks that can affect them in many ways. Risks like fire, theft, damage of assets, illegal intruders etc. can affect them strategically, financially and operationally. It can also damage their reputations. Educational institutions like Universities are also exposed to these risks. This research, through some real-life cases, studies on different types of risks that the Universities are exposed to. Malaysian universities were taken under consideration. The research focuses on the measures that these universities are taking in order to safeguard the several parties exposed to these risks. The paper also puts forward some recommendations that can mitigate these risks.